Failure narrative: Political peruvian novel of violence (1980-2000) - Vargas Yábar, Miguel (2014)
Failure narrative is a developing concept which describes the critical reading of the latest Peruvian narrative whose theme is structured around the political violence in our country in the period 1980-2000. It is conceptualized as a failure narrative basically for two reasons. On the one hand, because the ideological collision which results in the internal war makes evident the maximum point of disengagement and misunderstanding of the affirmative nuclei in the different voices involved in the comprehensive proposal of a Nation Project for Peru. On the other hand, because the rigidity of ideological positions is oriented towards an increasing mentality of war which tries to suppress the otherness, and prevail over it in a consistent and hegemonic way in a context of (cultural, linguistic and identity, etc.) diversities. The literature understudy, illustrates to what extent ‘official’ building proposals emerging in such period are twisted in destructive proposals that, despite its opposition, end up agreeing on the justification of a war ethos. Yet, this narrative accounts for a series of perspectives and experiences of different social actors. It also enables the critical review of the social and cultural coordinates in our country. The failure novel gives an account of the negative actions of the most important social actors of the nation, which converged on the outbreak of the civil war and had implications for the social disaster which Peru was sunk into in the period under study.